Identity construction and violence in Malay-Patani ethnonationalism in the dynamics of violations of international humanitarian law - Fiya Ainur Rohmatika; Ali Muhammad (Privietlab, 2025)
The Malay-Patani ethnonationalism conflict in Southern Thailand reflects the complex dynamics between identity construction, violence, and the violation of International Humanitarian Law (IHL). The background to the conflict is rooted in the political, cultural, and religious marginalization of the Malay-Muslim community by a Thai state that emphasizes the homogeneity of the Thai-Buddhist national identity. The suppression of the Malay language, religious institutions, and collective historical memory led to armed resistance and escalation of violence in the region. This research aims to analyze in depth how the construction of the Malay-Patani identity contributes to violence and forms of violation of the basic principles of IHL, such as distinction, proportionality, and necessity. This study used a descriptive qualitative method with a case study approach. Data were obtained through literature studies, reports from international organizations (International Committee of the Red Cross, Amnesty International, Human Rights Watch), and critical discourse analysis of identity narratives and violence. The results show that the construction of identity suppressed by state policy results in the legitimization of violence by separatist groups, while the state also responds with repressive actions that violate international humanitarian norms. Both state and non-state actors have been involved in systematic violations of IHL, including attacks on civilians, torture, and the use of banned weapons.